Effectiveness Of The Writing Poetry Guidebook with Pop-Up Book Media To The Student Learning Outcomes of Thrid Grade Students - Hartati, Hartati (Universitas Negeri Semarang, 2018)
AbstractThe purpose of this study was to determine the design, feasibility and effectiveness of a poetry writing guidebook with pop-up book media for third grade students. The type of this research was development research (R & D). The data taken were questionnaires on the needs of students and teachers, media and material validation, student learning outcomes, student and teacher responses to the developed guidebook. Small scale tests were carried out by Jambean 03 Elementary School with 8 students, and large scales test was conducted by Bumirejo 01 Elementary School with 32 students. The results showed that the guidebook developed had met the very feasible criteria with the results of obtaining 79.5% feasibility score from material experts and 98% from media experts. In the large-scale test the results of posttest students were got the classical completeness criteria that was equal to 100%. The calculation results got an average percentage of 97.22%. The increasing average was calculated using the N-Gain formula, with an average was 0.7 in the high category. The results of the teacher's response were 86.7% (very feasible) and the results of the students' responses were 96.3% (very feasible). It was concluded that the guidebook for writing poetry with pop-up book media for third grade students fulfilled the criteria of being very feasible and effective to be used in Indonesian language learning material for writing poetry third grade in second semester.